Authentication of Commercial Extra Virgin Olive Oils. (2nd February 2016) - Ok, Salim
Abstract: The goal of the current contribution is to determine the geographical origins of olive oil samples obtained from eight different countries during the harvest seasons of 2013 and 2014. First, the contents of olive oil samples were quantified by integrating the peaks of 1 H‐NMR spectra and using linear mathematical equations. The results were analyzed by analysis of variance (ANOVA), a statistical method examining whether there is a significant difference between the groups mean. The origins of the majority of the olive oil samples were discriminated by ANOVA and the minor constituents of the olive oils. Tocopherol and cycloartenol were the most discriminative minor constituents of the olive oil samples.